Nurses' and midwives' knowledge and practice of recommended evidence-based preterm care interventions in rural Kenya - Jane Wamuyu Kabo; Samwel Maina Gatimu; Johanna M. Mathibe-Neke (Elsevier, 2022)
Background: Approximately 25% of four million neonatal deaths globally are due to preterm birth, a majority occurring within the first week of life and, 60% in sub-Saharan Africa. Clinical interventions to improve preterm babies' outcomes are often not used. The study assessed the availability of preterm care guidelines and resources in rural public health facilities in Kenya and nurses/midwives' knowledge and practice of preterm care interventions as per the current preterm policies and guidelines in Kenya. Methods: A hospital-based cross-sectional design was conducted in 16 health facilities and among 102 nurses and midwives. Data were collected between January and March 2018 using the health assessment checklist and vignettes-based questionnaire. Frequencies and percentages were used to describe participants' characteristics, availability of guidelines, equipment and medicines, and knowledge, and practice on preterm care interventions. All analyses were performed using Stata 13. Results: Sixteen public health facilities and 102 nurses were assessed. The mean age and period of clinical practice were 36 (SD: 9) and 12 (SD: 10) years, respectively. 71 (70%) participants were females, and 78 (77%) registered nurses. Three-quarters (n = 76, 74.5%) of them had in-service training in newborn care within the last two years, majority 67% (n = 69) worked at health centres/dispensaries. Vitamin K and chlorhexidine were available only in 60.8% and 47.1% of the facilities respectively. Guideline's availability in facilities were 53%, 43%, and 32% for resuscitation, warmth provision, and breastfeeding within one hour respectively. None of the nurses would practice all the recommended preterm care intervention with 17 (16.7%) practicing none. The practice of the recommended preterm care intervention ranged from 7.6% for initiation of breathing to 29% for cord clamping, 32.4% use of chlorhexidine for cord care, 36.3% immediate feeding and 47.1% thermal protection. Conclusion: There exist gaps in the availability of medicines, equipment and guidelines for care of preterm babies, as well as implementation of evidence-based interventions to enhance the quality of care provided to preterm babies in the study area. We recommend increased provider-focussed strategies for improving the availability and implementation of low-cost high-impact evidence-based interventions for preterm care.